The Influence of 25 Training Sessions on the Decision-Making Skill of U-12 Soccer Players - Barcellos, Allan (2022)
The aim of this study was to verify the influence of 25 training sessions on the decision-making skill of U-12 soccer players. The sample was comprised of 25 U-12 soccer players from a first division Brazilian club. Decision making was assessed through the TacticUP® online platform. The 25 training sessions were organized based on the core tactical principles of soccer. There was a positive correlation (r=.413, p=.040) between the performance variation of decision-making and the training time for the offensive principles outside the center of play. It was concluded that training improved the decision-making skill of U-12 soccer players with respect to the tactical principles of width and length without the ball, mobility, and offensive unity.